A ecologia da paisagem e estratégias para ocupação e uso do solo: o entorno da RPPN Santuário do Caraça - Valesca Brandao Cerqueira Coimbra (2006)
The creation of protection areas is an efficient tool for nature preservation, mainly to minimize the impacts deriving of the spalling. This process, understood as the separation of the native nature into smaller and isolated parts, is considered to be one of the most serious enviroment problems of the present time, therefore it provokes the loss of biodiversity of a region. In Brazil, the ecosystem spalling reaches high ratios. One of the most affected enviromental area is Atlantic Forest, wich remains in about 7% of its original area. In recent years, an increase in the number of protection areas in Brazil can be perceived. However, the extension of the protected area is not apropriated for long term enviroment preservation , therefore most the units of preservationare located in areas of isolated remaining portions of native nature and they lack of interconnection with other natural sets. Thus, it is necessary to stand out the importance of the surrounding region of protection areas in order to allow the connection between the natural sets, in order to prevent the separation process and to contribute for the reduction of the spalling effect in ecosystems. These surrounding region, called buffer zone, is tied to the unit that includes both ecological and economic-cultural levels. Human activities in buffer zones generatenegative impacts that difficult the connectivity between protected areas, and, consequently, harm the maintenance of the biological diversity of that region. Thus, it is possible to formulate the following question: what strategies for the occupation and use of the ground in buffer zones ofprotection units aim to guarantee the connectivity between those areas? Planning a buffer zone must favor and, even though, extend the connection between natural sets, aiming the agreement between the human activities and natural processes. Thus, in order to subsidize this planning, the principles of the landscape ecology are used. This discipline possesss the landscape as the study object, and considers it an alive system that results from the interactions between the physicist,biological and anthropological events having the connectivity as its basic principle. In this work, the surrounding region of the particular reserve of Natural Patrimony Sanctuary of the Caraça was the study case. This unit of private conservation is situated in 120 km of Belo Horizonte, inthe cities of Santa Bárbara and Catas Altas in Minas Gerais State. The region presents a singular landscape quality, composed by mountainous scarps, mountain ranges, waterfalls, typical vegetation and native animals of transistion area between Atlantic Forest and Cerrado, diversityof species, scenic beauty landscapes and a rich historic-cultural site. However, such quality is being threatened by the impacts of the activities that occur in the surrounding region of the such area. The region is located into the domain of the Iron Square and withholds a significant mineral potential, what causes intense mining activity, and generate great enviroment impacts. Other activities are also distinguished, as forestry, farming and tourism. The analysis of the landscape structure of Sanctuary of the Caraça's surrounding region allows to inquire that the region was and is the place of great human interventions, where the enviroment is sliced, with some natural remaining portions. However, the high declivities and the rough relief provide the presence of anextensive natural area, constituted predominantly of elevated fields, with few anthropological interferences. Reserve of Caraça is located in this protected area together with an important unit of conservation and integral protection of the region called Parque Estadual do Itacolomi: theconnection between these two reserves is being kept. However, the future perspectives suggest an expansion of the human activities what can provoke the disruption of this natural matrix, hindering this connection, and creating the necessity to adopt strategies for the use andoccupation of this landscape aiming to revert this picture and to guarantee the long term preservation of the nature.